2020
DOI: 10.3389/fmicb.2019.03045
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an Intrinsic Mycovirus Associated With Reduced Virulence of the Human Pathogenic Fungus Aspergillus fumigatus

Abstract: Aspergillus fumigatus is an airborne fungal pathogen that causes severe infections with invasive growth in immunocompromised patients. Several mycoviruses have recently been isolated from A. fumigatus strains, but there are presently no reports of mycoviralmediated reduction or elimination of fungal pathogenicity in vertebrate models. Here, we report the biological features of a novel mycovirus, A. fumigatus chrysovirus 41362 (AfuCV41362), isolated from the hypovirulent A. fumigatus strain IFM 41362. The AfuCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 58 publications
(62 reference statements)
0
27
0
Order By: Relevance
“…However, previous studies have reported that the introduction of AfuCV (Jamal et al, 2010) or AfuPV-1 virus (Bhatti et al, 2011) to host fungi provoked no significant alterations of pathogenicity in murine infection models. Two exceptions are: (1) infection with AfuPmV-1 virus showed slight potentiation in pathogenicity in an insect infection model (Kanhayuwa et al, 2015), and (2) our previous report of chrysovirus, a different viridae from 1 https://talk.ictvonline.org/taxonomy/ the present work, showed reduced fungal virulence in a mouse model (Takahashi-Nakaguchi et al, 2020). Therefore, further mycoviruses that reduce A. fumigatus pathogenicity in a murine infection model remain to be detected (Özkan and Coutts, 2015).…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…However, previous studies have reported that the introduction of AfuCV (Jamal et al, 2010) or AfuPV-1 virus (Bhatti et al, 2011) to host fungi provoked no significant alterations of pathogenicity in murine infection models. Two exceptions are: (1) infection with AfuPmV-1 virus showed slight potentiation in pathogenicity in an insect infection model (Kanhayuwa et al, 2015), and (2) our previous report of chrysovirus, a different viridae from 1 https://talk.ictvonline.org/taxonomy/ the present work, showed reduced fungal virulence in a mouse model (Takahashi-Nakaguchi et al, 2020). Therefore, further mycoviruses that reduce A. fumigatus pathogenicity in a murine infection model remain to be detected (Özkan and Coutts, 2015).…”
mentioning
confidence: 57%
“…Furthermore (4), the growth of fungal hyphae and formation of conidia were retarded in the virus-infected strains in comparison with the virus-free strain during in vitro experiments. Incidentally, effects of AfuPmV-1M mycovirus infection on A. fumigatus were re-confirmed by introducing the mycovirus into the originally virus-free KU strain (AfS35, FGSC A1159, akuA:loxP) via the protoplast fusion method (Kanematsu et al, 2004;Lee et al, 2011;Takahashi-Nakaguchi et al, 2020). Tolerance to oxidative and osmotic stresses was decreased even in the whole virusintroduced strain (Supplementary Figure S8).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Beyond providing novel information on potential symbioses, mycovirus therapy presents a novel therapeutic solution for IFI, especially as resistance to anti-fungal treatments are on the rise ( Van De Sande et al, 2010 ). Success in the use of bacteriophage to treat respiratory bacterial infections suggest that parallel results could occur through the use of mycoviruses, which has been explored for Aspergillus therapy ( van de Sande and Vonk, 2019 ; Takahashi-Nakaguchi et al, 2020 ). Further discovery and characterizations of novel mycoviruses in Mucorales through -omics based approaches will not only offer a more complete biology of these fungi but may identify potential use of mycovirus therapy for mucormycoses.…”
Section: Future Directionsmentioning
confidence: 99%